EXTH-78. CRISPR/CAS9 KNOCKOUT SCREENS UNRAVEL EPIGENETIC REGULATORS AS DRUGGABLE DEPENDENCIES FOR SONIC HEDGEHOG MEDULLOBLASTOMA. (14th November 2022) - Tsiami, Foteini; Piccioni, Federica; Root, David; Bandopadhayhay, Pratiti; Segal, Rosalind; Tabatabai, Ghazaleh; Merk, Daniel
Abstract: Sonic hedgehog medulloblastoma (SHH-MB) is a malignant, highly heterogeneous brain tumor entity, accounting for 30% of all MBs in the pediatric population and is characterized by aberrant activation of the canonical SHH signaling pathway. Although current therapies targeting Smoothened ( Smo ) have proven a promising treatment approach for SHH-MB patients, pre-existing or acquired resistance impedes its clinical efficacy. Therefore, novel targeted approaches that overcome mechanisms of resistance are urgently needed. Here, we performed a genome-wide CRISPR/Cas9 knockout screen in a murine and a human SHH-MB cell line, SMB21 and DAOY, respectively, in order to decipher tumor-specific genetic essentialities. Our data demonstrate that SMB21 cells highly depend on key mediators of the SHH pathway, such as Gli2 ) for their proliferation, as opposed to DAOY cells, suggesting that the latter does not represent a faithful model of SHH-MB. Among other dependencies for SHH-MB are members of the epigenetic machinery such as Dnmt1 ) and Smarca5 ). Pharmacologically, we show that DNMT1 inhibition is efficacious at clinically relevant concentrations against Smo inhibitor- sensitive, as well as resistant SHH-MB cell lines. By performing RNA sequencing of SMB21 cells, we identified early and late alterations in global gene expression induced by DNMT1 inhibition, including decreased expression of positive regulators of SHH signaling. An additional knockout drug screen in SMB21 cells unraveled synthetic lethal interactors for DNMT1 inhibitors, as validated in vitro ) by drug combination treatments. Further global DNA methylation profiling in SMB cells will help to define the molecular basis of sensitivity to DNMT1 inhibitors in SHH-MB. Last but not least, genetic ablation of epigenetic regulators and combinatorial treatments using DNMT1 inhibition will be investigated in in vivo ) established mouse models of SHH-MB. Summarizing, our data indicate the potential of inhibiting epigenetic regulators as novel therapeutic avenues in SHH-MB sensitive, as well as resistant to Smo inhibition.